Examining Relationships between School Administrators’ Humor Behaviors and Teachers’ Mobbing Experiences According to Teacher Perceptions - Cemaloğlu, Necati; Şahin, Fatih; Recepoğlu, Ergün; Daşcı, Elif (International Online Journal of Educational Sciences, 2014)
The purpose of this study was to identify school administrators' humor behaviors as perceived by teachers and to determine the relationships between the school administrators' perceived humor behavior and mobbing experienced by teachers. Data was obtained from 459 teachers chosen by systematic sampling. Results indicated that teachers described negative attitudes mostly encountered as "refusal to take their ideas and opinions into consideration," "hiding information that would affect their performance from them", and "humiliation suffered as a result of being assigned to works below the level of their competence." Teachers believed that school administrators generally had "Appreciative humor" and "productive-social humor" attitudes. While there was a negative and significant relationship between positive humor behaviors and mobbing, there were also positive and significant relationships between negative humor behaviors and mobbing. Sarcastic humor and rejective humor were the significant predictors of mobbing. © 2014 IOJES. All rights reserved
Keywords: 13. Climate action; 4. Education